2024
DOI: 10.1111/cid.13302
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo accuracy of autonomous robotic vs. fully guided static computer‐assisted implant surgery

Jin He,
Qinmeng Zhang,
Xueting Wang
et al.

Abstract: ObjectivesTo assess the accuracy of autonomous robotic and fully guided static computer‐assisted implant surgery (sCAIS) performed on models and patients.Materials and MethodsThis study was divided into in vitro and in vivo sections. In vitro, 80 operators were assigned to two groups randomly. Forty operators performed forty autonomous robotic implant (ARI group) surgeries and the remaining forty operators carried out forty fully guided sCAIS (FGI group) surgeries on maxillary models, respectively. Each operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…However, in vitro studies cannot fully simulate the patients’ oral condition and bone quality. Recent clinical studies 89 , 92 , 93 have shown a lower deviation in robotic-assisted implant placements compared to static-guided and dynamic-navigated implant placements. Common reasons for deviations in static-guided and dynamic-navigated implant placements include the following: deflection caused by hand tremors due to dense bone during surgery, surgeons’ experience, and other human factors.…”
Section: Dental Implant Robotic Systemmentioning
confidence: 99%
“…However, in vitro studies cannot fully simulate the patients’ oral condition and bone quality. Recent clinical studies 89 , 92 , 93 have shown a lower deviation in robotic-assisted implant placements compared to static-guided and dynamic-navigated implant placements. Common reasons for deviations in static-guided and dynamic-navigated implant placements include the following: deflection caused by hand tremors due to dense bone during surgery, surgeons’ experience, and other human factors.…”
Section: Dental Implant Robotic Systemmentioning
confidence: 99%